What, what for and how? Developing measurement instruments in epidemiology - Michael Reichenheim; João Luiz Bastos (Universidade de São Paulo, 2021)
ABSTRACT The development and cross-cultural adaptation of measurement instruments have received less attention in methodological discussions, even though it is essential for epidemiological research. At the same time, the quality of epidemiological measurements is often below ideal standards for the construction of solid knowledge on the health-disease process. The scarcity of systematizations in the field about what, what for, and how to adequately measure intangible constructs contributes to this scenario. In this review, we propose a procedural model divided into phases and stages aimed at measuring constructs at acceptable levels of validity, reliability, and comparability. Underlying our proposal is the idea that not only some but several connected studies should be conducted to obtain appropriate measurement instruments. Implementing the model may contribute to broadening the interest in measurement instruments and, especially, addressing key epidemiological problems.